(3GNJUGQ fRgI GdeTJGb aj GNJQGb GdBaGbs - (3eLghds; (3GdEOQjSj , eMeO Hf eMeO Hf YHO Gddg Hf EOQjS GdMSfj GdWGdHj, CHh YHO Gddg,J (B560 (3g` s
(3ChdgG (B:s
(3CeG HYO Efi hbaJ Ydi GdcJGH GdeSei HfRgI GdeTJGb ai GNJQGb GdBaGb s
(3BNQgG (B:s
(3GeG JNQL Edi ef jWQM efge ef cgha ai LfHJi GdhGOi s
(3HgG fXGe GdJYbjHIs
(3PcQ GdYfhGf GdCUdi ai cX (B2/ 1947s
(3JHUQI GdYfhGf (B:s
(3ENJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B24 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B236s
Keywords: (3GdLZQGajG h GdHdOGfs